ANALISIS RAGAM GENETIK, HERITABILITAS, DAN SIDIK LINTAS KARAKTER AGRONOMIK JAGUNG HIBRIDA SILANG TUNGGAL - Priyanto, Slamet Bambang; Azrai, Muhammad; Syakir, Muhammad (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2018)
The success of selection in plant breeding program is determined by genetic variabiliities, heritability values and the correlation between agronomic characters and yield. The study aims to determine the genetic variability, heritability and the effec of agronomic characters to grain yield. The experiment was conducted in February to May 2016 in Grobogan, Central Java. The experiment consists of twelve genotypes of maize hybrids, arranged in a randomized block design with three replications. The characters observed were plant height, ear height, number of harvested ear, shelling percentage, moisture content of grain harvested, weight of 100 grains, ear length, ear diameter, number of rows per ear, number of seeds per row per ear, and grain yields. The results showed that the genetic variability of agronomic characters was broad, except ear diameter. Almost all of the heritability values of yield components were high, except harvested ear weight and ear diameter. The characters of plant height, ear height and as the genotypic gave high of a direct effect on the yield higher, while direct effect of the phenotypic character of ear hairves on grain yield are higher.